2021
DOI: 10.1515/chem-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism underlying sevoflurane-induced protection in cerebral ischemia–reperfusion injury

Abstract: Cerebral ischemia is an extremely complex disease that can be caused by a variety of factors. Cerebral ischemia can cause great harm to human body. Sevoflurane is a volatile anesthetic that is frequently used in clinic, and has a lot of advantages, such as quick induction of general anesthesia, quick anesthesia recovery, no respiratory tract irritation, muscle relaxation, and small cycle effect. The mechanism of sevoflurane preconditioning or post-treatment induction is poorly understood. The purpose of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…It is suggested that mice aged 6 days postnatally have brains that are more vulnerable than those of older mice. Another study highlighted that sevoflurane acts like a double-edged sword; on the one hand, it can cause neuroinflammation, but on the other, it has a neuroprotective effect, which also involves the mechanism of NF-κB activation (14). PSD-95 levels, a protein marker of brain plasticity, experienced a significant increase in the sevoflurane-J Cell Mol Anesth.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that mice aged 6 days postnatally have brains that are more vulnerable than those of older mice. Another study highlighted that sevoflurane acts like a double-edged sword; on the one hand, it can cause neuroinflammation, but on the other, it has a neuroprotective effect, which also involves the mechanism of NF-κB activation (14). PSD-95 levels, a protein marker of brain plasticity, experienced a significant increase in the sevoflurane-J Cell Mol Anesth.…”
Section: Discussionmentioning
confidence: 99%